"Santa" Maria Féa e o culto popular: análise da divulgação de milagreiros pela mídia impressa local - Mello, Lilian de Jesus Assumpção (2006)
Study on the media coverage of subjects related to the character of Maria Fea, considered Brazilian non-canonical saint, from 1994 to 2004. The objective was to analyze the manifestations (ex votes) attributed to the creed to this ersonagem, the disclosure of subjects about the character in a local newspaper, besides making a historic rescue.